METODE DAKWAH MUHAMMADIYAH DI KABUPATEN TAPANULI SELATAN - MOHD. RAFIQ (Institut Agama Islam Negeri Padangsidimpuan, 2016)
To actualize a successfull da’wa, Muhammadiyah has formulated various methodologies appropriately to the people in their lifes. For the first work, Muhammadiyah eradicates hard the three aspects; takhyul, bid’ah, and khurafat. Da’wa of Muhammadiyah is intended to restore the understanding and practicing of Islam rules based on the Qur'an and Sunnah. The successfull of da’wa which is characterized by the practice of Islam in the mental and spritual aspects can be reached when the methodology of da’wa can be accepted by the people. There are several methods of da’wa applied by Muhammadiyah in South Tapanuli; they are al hikmah, Al mau’izhatil hasanah, and mujadalah. The three methods implemented in da’wa bil lisan, da’wa bil kitabah, da’wa bil hal and da’wa cultural. Although in implementing them Muhammadiyah faces hard chalenges from many people, it keeps trying to restore the understanding and practicing of Islam rules based on Al’Qur’an and Sunnah.